2017
DOI: 10.1002/ejoc.201700239
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Chiral Borate Counteranion, Its Trityl Salt, and Application Thereof in Lewis‐Acid Catalysis

Abstract: The preparation of a chiral derivative of [B(C6F5)4]– in which the fluorine atom in the para position of each of the C6F5 groups is replaced by a 1,1′‐binaphthalen‐2‐yl group is described. The new counteranion was isolated as its lithium, sodium, and trityl salts. The chiral trityl salt was then used as a catalyst in selected counteranion‐directed Diels–Alder reactions and a Mukaiyama aldol addition, but no asymmetric induction was achieved. Application of the chiral trityl salt to the generation of silicon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Chiral congeners of these anions are essentially unknown but their use as chiral counteranions in asymmetric catalysis is attractive. Recently, we and List and co‐workers independently introduced chiral versions of [B(C 6 F 5 ) 4 ] – where the fluorine atoms in the para positions have been replaced by 1,1′‐binaphthalene‐2‐yl groups (Figure , left) , . We showed that the trityl salt of [ 1 ] – promotes Diels–Alder reactions as well as a Mukaiyama aldol addition but we did not observe any enantioselectivity .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Chiral congeners of these anions are essentially unknown but their use as chiral counteranions in asymmetric catalysis is attractive. Recently, we and List and co‐workers independently introduced chiral versions of [B(C 6 F 5 ) 4 ] – where the fluorine atoms in the para positions have been replaced by 1,1′‐binaphthalene‐2‐yl groups (Figure , left) , . We showed that the trityl salt of [ 1 ] – promotes Diels–Alder reactions as well as a Mukaiyama aldol addition but we did not observe any enantioselectivity .…”
Section: Introductionmentioning
confidence: 91%
“…Recently, we and List and co‐workers independently introduced chiral versions of [B(C 6 F 5 ) 4 ] – where the fluorine atoms in the para positions have been replaced by 1,1′‐binaphthalene‐2‐yl groups (Figure , left) , . We showed that the trityl salt of [ 1 ] – promotes Diels–Alder reactions as well as a Mukaiyama aldol addition but we did not observe any enantioselectivity . Similar observations were made by List and co‐workers; however, when shifting the chiral unit from the para to the meta position as in [ 2 ] – , a Mukaiyama aldol reaction afforded 16 % ee as proof of concept…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pursuit of this approach has met with limited success. [15][16][17] The borate ion such as tetraarylborate is a representative WCA that is widely used as the counterion for a variety of cationic species. In particular, tetraalkoxyborates (B(OR) 4 − ) constitute a venerable class of borates for developing chiral WCAs because these structurally diverse ions can be easily prepared by the condensation of boric acids (esters) with various chiral alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…stability, solubility, and chirality) beyond what these simple species allow. To this end, notable advances have been made in the development of effective chiral anions, 4 extremely stable anions such as carboranes 5 and perfluoroborates, 6 and complex counterions generated via anion binding. 7 Despite these important advances, there remains an important need for new, highly stable, readily accessible, and broadly diversifiable anion frameworks.…”
Section: Introductionmentioning
confidence: 99%